﻿The in vitro equivalence study of polymorph-modified glimepiride tablets compared to Amaryl® - Fitrianti Darusman; Taofik Rusdiana; Iyan Sopyan; Ratih Aryani; Gita Cahya Eka Darma (Pensoft Publishers, 2023)
Glimepiride (GMP) is an oral antidiabetic drug classified as BCS class II, demonstrating extremely limited solubility, with a solubility level below 0.00384 mg/mL. Some generic drug manufacturers producing GMP (copy product) tablets encountered bioavailability issues due to poor dissolution, which did not meet the requirements. Therefore, measures were taken to enhance solubility through the modification of polymorphs. It is known that GMP exists in two polymorphic forms, namely Form I and an alternative Form II, which exhibits higher solubility in water. This study aims to produce and characterize the polymorph-modified GMP compared to non-modified GMP, develop an optimal formulation for polymorph-modified GMP tablets that adhere to pharmaceutical requirements as a representative copy drug model, and determine its similarity factor to Amaryl® as the innovator. The research methodology involved initiating the study by examining the polymorph transformation of GMP through the utilization of techniques such as neat grinding, solvent drop grinding, and solvent evaporation. The resulting samples were characterized using DSC, PXRD, and SEM analysis. The performance assessment encompassed the evaluation of flow properties, compressibility index, solubility, and dissolution rate compared to the non-modified GMP. Based on the characterization results, the best polymorph-modified GMP sample was used to produce a tablet formulation containing 4 mg of GMP using the direct compression method as a copy tablet model. In vitro equivalence testing was performed using a comparative dissolution test on the polymorph-modified GMP tablet compared to its innovator, Amaryl® 4 mg, in three different dissolution media, followed by determining the equivalence status using the similarity factor (f2) calculation. Based on the screening results of polymorph transformation, it was determined that the polymorph-modified GMP, using all three techniques, did not undergo a transition from Form I to Form II. Instead, it underwent amorphization, primarily observed in the solvent evaporation technique. Tablets containing polymorph-modified GMP using the solvent evaporation technique were able to enhance the in vitro dissolution rate profile compared to non-modified GMP tablets. The f2 values for the comparative in vitro dissolution test in acetate buffer pH 4.5 and phosphate buffer pH 6.8 were 60.15 ± 0.27 and 88 ± 0.35, respectively within acceptance criteria of 50-100. However, in KCl/HCl buffer pH 1.2, the f2 value was 45.15 ± 0.23. It was concluded that the polymorph-modified GMP tablet was not similar to its innovator, Amaryl®.